Design of a Switching Flyback Transformer as High Voltage and Frequency Power Supply for Raw Milk Cold Plasma Sterilization - Fajar, Muhamad Ibnu; Elfahra Casanza Amalda; Muhammad Ali Akram Syah; Nurussa’adah (Publisher Cv. Inara, 2020)
Plasma is one of the four fundamentals states of matter other than solid, liquid and gas. In terms of temperature, plasma can be classified into Hot Plasma occurs in thermal equilibrium, Thermal Plasma occurs in non-thermal equilibrium, Cold Plasma occurs in non-thermal equilibrium Cold plasma is an ultra-fast method of sterilization that operates under ambient temperatures (ideal for thermolabile products) at a low running cost and is environment-friendly. Therefore, technology is needed to solve the problem through the innovation of a milk sterilization machine with the principle of non-thermal plasma sterilization by utilizing plasma technology to reduce microbial contamination. The output frequency and voltage are determined through software simulation using voltmeter, oscilloscope, and counter timer. After 220VAC supplies a voltage step down and rectifier circuit to produce a 12VDC output voltage to supply the Switching circuit voltage and the Flyback Transformer driver. Rated voltage and frequency reach 20kV 15kHz.The positive wire from the Flyback Transformer is connected to the acrylic box filled with water (positive electrode) and the ground wire is connected to another acrylic sheet (ground electrode. The milk medium to be sterilized can be placed on the positive electrode or between the ground and positive electrodes. Non-thermal plasma has an effective ability to decontaminate bacteria. This is because plasma is composed of a mixture of ionized particles, reactive radical molecules, and also ultraviolet Schematic circuit design has been successfully simulated. Acrylic sterilization media designs can be used to generate plasma. The mechanism of bacterial sterilization in milk is by the activity of inhibiting bacterial biofilms which can lead to bacterial DNA damage through reactive species in the non-thermal plasma used. Milk quality testing is carried out based on comparison of supporting literature with milk quality requirements according to SNI 3950: 2014.